Micropumps for Microfluidic Devices and BioMEMS. (October 2020) - Huo, Cheng; Bai, Chenlin; Zhang, Peiyu
Abstract: The development of micropumps are reviewed and their applications are summarized. The micropumps are categorized into indirectly-driven and directly-driven micropumps according to the ways of driven origination from working principles. The actuation principles are introduced in detail including electrostatic, piezoelectric, thermopneumatic actuation, etc. Moreover, the performance influencing parameters on the property and the applications of various micropumps for medical therapy are described such as reciprocating, peristaltic, rotary, electrohydrodynamic, micropumps, etc. The challenge of micropumps is also discussed.